Genetic Regulation of Plasma Levels of Vitamin K-dependent Proteins Involved in Hemostasis - Souto, Juan Carlos; Almasy, Laura; Blangero, John; Stone, William; Borrell, Montse; Urrutia, Teresa; Mateo, José; Fontcuberta, Jordi (Thrombosis and Haemostasis, 2001)
Vitamin K-dependent proteins play a critical role in hemostasis. We have analysed the genetic and environmental correlations between measures of several vitamin K-dependent proteins in 21 Spanish extended families, including 397 individuals. Plasma functional levels of factors II, VII, IX, X, protein C and functional protein S were assayed in an automated coagulometer. Antigenic levels of total and free protein S were measured using an ELISA method. A maximum likelihood-based covariance decomposition analysis was used to assess the heritability of each trait and the genetic and environmental correlations between all possible pairs. All of the plasma levels had a significant genetic component (heritability) ranging from 22% to 52% of the phenotypic variance. Among the 28 possible pairs of genetic correlations, 18 were significant at a level of p <0.05 and six exhibited a p-value between 0.05 and 0.10. Positive environmental correlation was observed for 25 of the pairs (p <0.05). We conclude that genetic effects account for a large proportion of the observed phenotypic variation in vitamin K-dependent proteins. Some of the genes appear to pleiotropically influence all of these traits, since most pairs of phenotypes exhibit significant genetic correlation. However, since these phenotypes show a high degree of environmental correlation, it is also likely that the same environmental factors influence them co-jointly.
Keywords: Vitamin K; thrombosis; genetic correlation; heritability; pleiotropy